Avaliação da utilização de camada porosa de atrito em vias do meio urbano - Alecrim, Carla Marília Cavalcante (2021)
Sustainability in paving has gained importance, among other reasons, due to the need to reduce the environmental impacts, i.e.: depletion of natural resources, generation of waste, air pollution, noise pollution, waterproofing of surface, creation of heat islands, among others. In this context, there are numerous paving solutions that offer better suitability for sustainability requirements, for instance, the recycling of asphalt mixtures, the functionalization of the pavement, and the use of porous asphalt. Among the latter, there is the Porous Friction Course (PFC), which is a type of wearing course used mainly on highways and on runways. The main function of this type of surface is to provide functional improvements to the pavement. The objective of the present work is to evaluate the use of PFC in urban roads, in which they are not commonly used. In order to achieve this purpose, the compliance with the mechanical properties required in Brazil for PFC was verified in the laboratory, for virgin and recycled mixtures; a structural analysis of the pavement containing this type of wearing course was carried out, using the software MeDiNa (AEMC); and, finally, an analysis of the performance of the PFC in the field regarding the following properties was performed: acoustic (using the controlled pass-by method), surface (using sand patch, British pendulum and 3D modeling methods) and drainability. The results suggest that the incorporation of 15% of reclaimed asphalt in PFC did not affect the behavior of the asphalt mixture when compared to reference virgin mixtures. However, both cases presented Indirect Tensile Strength (ITS) values of 0.47 MPa, which is lower than the minimum value required (0.55 MPa) by the Brazilian standard. The structural analysis showed that the availability of a layer of PFC at the top of the pavement reduces the tensile strain in the lower fiber of the underlying asphalt layer and the compression at the top of the subgrade by up to 26 and 22%, respectively. This allowed an increase in the number of cycles until the rupture of the pavement by the mechanisms of fatigue and permanent deformation. The analysis of the acoustic performance in the field showed that there was a reduction of up to 5.6 dB (A) in the tire-pavement noise with the use of PFC in comparison to the traditional Asphalt Concrete (AC) dense layers. Traditional tests for micro and macrotexture showed that the PFCc, with 2 to 2.5 years in service, had similar characteristics of a traditional AC coating. They were classified as medium in terms of macrotexture, and smooth in terms of microtexture. 3D modeling of the asphalt surface provided better sensitivity to the negative texture of PFC, which can be better evaluated using ISO 25178-2 (2012) parameters, e.g., skewness (Ssk) and kurtosis (Sku). The drainability test also showed similarities between PFCs and traditional AC.